ANALISIS FINANCIAL DISTRESS DENGAN MENGGUNAKAN METODE ALTMAN Z-SCORE, SPRINGATE, ZMIJEWSKI PADA PT GARUDA INDONESIA (PERSERO) TBK PERIODE 2018-2021 - Alfiansyach, Ari; Muyassaroh, Muyassaroh (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2025)
This study aims to determine how the condition of the financial performance of PT Garuda Indonesia (Persero) Tbk for the 2018-2021 period if measured using the Altman Z-Score, Springate, Zmijewski methods, and to analyse the corporate actions taken by PT Garuda Indonesia (Persero) Tbk for the 2018-2021 period. This study uses secondary data, taken from the annual financial statements of PT Garuda Indonesia (Persero) Tbk for the 2018-2021 Period, using comparative descriptive analysis techniques, carried out by analysing the condition of Financial Distress when measured by the Altman Z-Score, Springate, Zmijewski methods. The results showed that PT Garuda Indonesia (Persero) Tbk from 2018 to 2021 experienced financial distress when measured using the Altman Z-Score, Springate, Zmijewski methods, and the corporate actions taken did not have a significant impact to PT Garuda Indonesia (Persero) Tbk, and the most severe financial distress conditions experienced by PT Garuda Indonesia (Persero) Tbk in 2020 and 2021 as a result of the Covid-19 pandemic.Keywords: Financial Distress, Altman Z-Score, Springate, Zmijewski